2013
DOI: 10.18285/geonomos.v16i1.91
|View full text |Cite
|
Sign up to set email alerts
|

Titanite Crystal Chemistry and U-P Isotopic Data: A Petrogenetic Indicator for Precambrian Granitoid Plutons of the Eastern Brazilian Shield

Abstract: This paper presents crystal chemistry and U-Pb isotopic data for titanite (or sphene, CaTiSiO 5 ) from Precambrian granitoid plutons of distinct tectonic settings within the Eastern Brazilian shield. Despite the fact that most titanite ages are related to partial lead-loss, resetting or crystallization during metamorphic events, chemistry data reflect the magmatic history of the plutons, specially the Ti 4+ /Al+Fe 3+ ratio. It is demonstrated that for plutons of different crystallization ages (Archean, Paleopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…ca. 528Ma, assim como a amostra de titanita de um ortognaisse mais velho (2867 ± 10 Ma, Silva et al 2002), mas do mesmo complexo, forneceu a idade de 506 ± 7 Ma (Piuzana et al 2008). Além disso, Oliveira (2002) obteve uma idade isocrônica Sm-Nd (rocha total-granada) de 521 ± 21 Ma para o metamorfismo de um gnaisse arqueano e Ribeiro-Althoff et al (1997) determinaram a idade Ar-Ar (de inclusões de flogopita em esmeralda) de 509 ± 2 Ma para o depósito de Capoeirana.…”
Section: -Amostra #8: Ortognaisse Tonalítico De São João Evangelistaunclassified
“…ca. 528Ma, assim como a amostra de titanita de um ortognaisse mais velho (2867 ± 10 Ma, Silva et al 2002), mas do mesmo complexo, forneceu a idade de 506 ± 7 Ma (Piuzana et al 2008). Além disso, Oliveira (2002) obteve uma idade isocrônica Sm-Nd (rocha total-granada) de 521 ± 21 Ma para o metamorfismo de um gnaisse arqueano e Ribeiro-Althoff et al (1997) determinaram a idade Ar-Ar (de inclusões de flogopita em esmeralda) de 509 ± 2 Ma para o depósito de Capoeirana.…”
Section: -Amostra #8: Ortognaisse Tonalítico De São João Evangelistaunclassified
“…8e) and high Sr, Zr and Nb contents. High Ti 4+ / Al + Fe 3+ ratio (>11) is indicative of mantle-related source regions (Piuzana et al 2008) and values >18 are demonstrated exclusively by LAM2 titanite (among all studied samples). High (Ce + Nd)/Y, La/Ce and low Nb/Zr, Y/Zr and Lu/Hf ratios have been documented in titanite from mafic rocks and MMEs of the Mangling granitoid pluton (Hu et al 2017) and from intermediate rocks and MMEs of the Ross of Mull granite (McLeod et al 2011), which both originated by mixing of mantle-and crust-derived sources.…”
Section: Characteristics Of Mafic Mantle-related Titanitementioning
confidence: 78%
“…Apart from rare earth elements, major and other trace element concentrations and ratios also show some affinity to the mafic mantle-related titanite. Ti 4+ /(Al + Fe 3+ ) ratios are usually >9 (and overlap with some of the LAM2 titanite grains) for FOJ titanite, suggesting significant mantle contribution Piuzana et al (2008) (Fig. 6).…”
Section: Early Stages Of Magmatic Evolutionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fernandes (2001) presented the titanite age of ca.507 Ma (U-Pb TIMS) for the Statherian Borrachudos anorogenic granitoid. Piuzana et al, (2008) reported the titanite age of 506 ± 7 Ma for the trondhjemite gneiss of the Guanhães complex located south of the Capelinha region. Silva et al, (2011), for the biotite orthogneiss of the Guanhães complex situated at São João Evangelista town, presented the zircon age of 527 ± 45 Ma (U-Pb SHRIMP, inferior intercept).…”
Section: Acknowledgmentsmentioning
confidence: 99%